Four new species of Azygophleps Hampson, 1892 (Lepidoptera, Cossidae, Zeuzerinae) from Africa - Yakovlev, Roman V.; Witt, Thomas J. (Zootaxa, 2017)
Azygophleps snizeki Yakovlev & Witt, sp. nov. (type locality Kenya, E of Mwingi, W of Enguni), Azygophleps wahlbergi Yakovlev & Witt, sp. nov. (type locality Kenya, Garissa, S of Bura), Azygophleps defreinai Yakovlev & Witt, sp. nov. (type locality South Africa, KwaZulu Natal Prov., Südl. Drakensberge Region, 30 km SSW Underberg, Coleford Nature Reserve) and Azygophleps junkeri Yakovlev & Witt, sp. nov. (type locality Angola, prov. Benguela, btw Cutembo & Caluquembe, 14 km E Cutembo) are described.